(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article is devoted to the formation of public relations organizations in Kurdistan-Iraq, the formation of their goals, objectives, functions and specialization, as well as the practice of PR in the Kurdish media, including the Rudaw media corporation. It shows the processes and methods of strategic planning of the content of Kurdish media corporations with the mandatory participation of PR departments. The article also analyzes the reasons for the shortcomings in the strategic planning of media content in the Kurdish media due to the neglecting of the role and tasks of public relations services. Key words: public relations, media content, Kurdish media corporations, Rudaw media corporation. DOI 10.18522/1995-0640-2020-2-226-235